Desarrollo sostenible e ingresos petroleros: un estudio para los países productores de petróleo en América Latina, periodo 1990-2020. - Ruiz Carrasco, David Fernando (2023)
This research starts with the purpose of determining the impact of oil revenues on the sustainable development of oil-producing countries in Latin America, period 1990-2020, in said study the following variables were used, HDI or Human Development Index as dependent, while the independent variables considered were oil income, health spending, and savings. Thus, this research is made up of four chapters, where the first chapter refers to the introductory part of the topic raised, its main problem and also covers the general and specific objectives considered in this study, as for chapter II, it is presents the theoretical part where concepts, calcifications and the main contributions of economic schools on the subject of sustainable development are exhibited. Therefore, in the third chapter the methodological part of the research is presented, that is, this section explains how to proceed with the data collection, the type of research, the design, and above all, the type of econometric model is described. which will be used to achieve the research objective, which is an autoregressive model of distributed lags ARDL, and finally in the last section the conclusions and recommendations are described according to the findings found in the econometric estimation.